Small and large for gestational age condition as a risk factor for neonatal morbidity and mortality at term newborns at altitude - Villamonte-Calanche, Wilfredo (2022)
Background: The fetus growth at high altitude is less than at sea level due to hypobaric hypoxia. Consequently, there are small neonatal anthropometric measurements. Therefore, there is no information about predicting neonatal morbi-mortality using Battaglia and Lubchenco criteria by neonatal curve created at 3400-m altitude (TANA). Material and Methods: It was a case-control study. We used the information of 16000 term infants from the Adolfo Guevara Velazco National Hospital in Cusco, from January 1, 2003, to June 30, 2012. We evaluated the 3rd, 10th, 90th, and 97th percentile (P3, P10, P90, and P97) of newborns weight and ponderal index (PI). Neonatal anthropometry less than P3 or P10 (SGA) and higher than P90 or P97 (LGA) were the cases, and those with measurements between these intervals were the controls (AGA). Results: SGA (P10) prevalence was 9.6% and 10.7% of LGA (P90). The P3 of the birth weight (BW) increases the risk of occurrence of neonatal morbidity and mortality in 3.2 and 10.7 times, respectively. Similarly, it prognosticates longer hospital stay (6.2 days). Conclusions: Applying the Lubchenco and Battaglia criteria and P3 and P97 of the BW and PI using the TANA, we determined that the P3 of the BW defines the highest risk for neonatal morbidity and mortality at term newborns at 3400-m altitude